Evaporation of sulfate aerosols at low relative humidity - G. Tsagkogeorgas; P. Roldin; P. Roldin; J. Duplissy; J. Duplissy; L. Rondo; J. Tröstl; J. G. Slowik; S. Ehrhart; S. Ehrhart; A. Franchin; A. Kürten; et al. (Atmospheric Chemistry and Physics, 2017)
Evaporation of sulfuric acid from particles can be important in the atmospheres of Earth and Venus. However, the equilibrium constant for the dissociation of H2SO4 to bisulfate ions, which is the one of the fundamental parameters controlling the evaporation of sulfur particles, is not well constrained. In this study we explore the volatility of sulfate particles at very low relative humidity. We measured the evaporation of sulfur particles versus temperature and relative humidity in the CLOUD chamber at CERN. We modelled the observed sulfur particle shrinkage with the ADCHAM model. Based on our model results, we conclude that the sulfur particle shrinkage is mainly governed by H2SO4 and potentially to some extent by SO3 evaporation. We found that the equilibrium constants for the dissociation of H2SO4 to HSO4−(KH2SO4) and the dehydration of H2SO4 to SO3 (xKSO3) are KH2SO4 = 2–4 × 109 mol kg−1 and xKSO3 ≥  1.4  ×  1010 at 288.8 ± 5 K.